Laboratory Testing and Evaluating of Shale Interaction with Mud for Tanuma Shale formation in Southern Iraq - AlShibli, Fadhil H.; A. Alrazzaq, Ayad A. Alhaleem (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
Rock failure during drilling is an important problem to be solved in petroleum technology. one of the most causes of rock failure is shale chemical interaction with drilling fluids. This interaction is changing the shale strength as well as its pore pressure relatively near the wellbore wall. In several oilfields in southern Iraq, drilling through the Tanuma formation is known as the most challenging operation due to its unstable behavior. Understanding the chemical reactions between shale and drilling fluid is determined by examining the features of shale and its behavior with drilling mud. Chemical interactions must be mitigated by the selection of suitable drilling mud with effective chemical additives. This study is describing the laboratory methods that concern testing and evaluating the shale instability encountered while drilling operations. The cutting samples are collected from the targeted formation and used to categorize shale reactivity levels and the required additives to inhibit the clay instability. These tests include the descriptive method with the various analytical technique of standard laboratory equipment. The shale testing techniques are the Scanning Electron Microscope (SEM), X-ray Diffraction, X-ray Fluorescence, Cation-Exchange, Capacity (CEC), and Capillary Suction Timer test (CST). Also, Linear swelling meter test (LSM) was performed to enhance the development plan. Tanuma formation contains moderately active clay with the presence of microfractures and micropores in its morphology. And it is controllable by using polymer muds with 8 % of inorganic inhibitor (e.g., KCL), filtration controls additives, and poly amino acid hydration suppressant which showed minimum swelling percentage.